Development and Reliability of Parents' Body Posture Literacy Questionnaire (PBPLQ) - Marta Kinga Labecka; Agnieszka Jankowicz-Szymanska; Elzbieta Olszewska; Magalena Plandowska; Piotr Tabor; Reza Rajabi (Rehabilitacja Medyczna)
Introduction: Postural defects are a serious problem in modern society. In research on the subject, it is indicated that parents should pay special attention to their children's body posture. Basic knowledge in the field of posture defects and prevention will help prevent and deal with postural defects in children.Objectives: The aim of the study is to design and determine the reliability of a questionnaire examining parents' knowledge of postural health.Material and methods: The questionnaire development process consisted of the following steps: content and face validation, as well as reliability analysis. The questionnaire contains items assessing parents' literacy of body posture and was conducted among 55 Polish parents of school-age children and adolescents.Results: Initial results (first test-retest) for 37 participants revealed substantial reliability (0.61 to 1.00), however, it was exhibited that modifications were needed for some specific questions. After revisions and retesting (second test-retest of 18 participants), the updated questionnaire demonstrated significantly improved reliability (Cohen's kappa coefficient ranged from 0.85 to 1.00).Conclusions: The developed questionnaire is valid in terms of face and content validity, as well as reliability for assessing parents' literacy of body posture, and can potentially be used in clinical trials and practical settings.